Changing Practices of the State: Johannesburg City Parks and Zoo Officials’ Views on Opportunities and Challenges of Community Engagement - Bosaka, Patience (University of the Witwatersrand, Johannesburg, 2015)
South African cities are embedded in a paradigm of transformation, informed by post- apartheid aspirations, good governance principles, and the value of community engagement in a democratic context. The Parastatal Johannesburg City Parks and Zoo situated in this broader context thus also envisage transformation in their ways of urban governance. This research takes interest in the institutional reshuffling of JCPZ that has resulted in their move towards the promotion of community development in the management and development of urban parks. The reshuffling aims to respond to pressing issues such as mismanagement, crime, homelessness, unemployment, vandalism inter alia which manifest in public green spaces, showcasing inequalities and poverty in ways that are difficult to manage. One of the strategies that are emphasized in responses to these issues is community engagement which is the arena that grounds this research investigation. The paper looks at JCPZ officials’ practices, challenges and experiences in their mandate of community engagement and demonstrates the importance of structure (the institutional programmes and systems put in place for this task) and perceptions (what officials’ feel and think about communities) as influential to the actual State practices. It also reviles the other side of the story (the officials’ narratives) about community engagement which is hardly documented in community engagement discourses.
Planning Honours Report 2015, Wits University
Keywords: community engagement, Johannesburg City Parks and Zoo, governance, citizens, participation, state practices